Surface Passivation of Perovskite Film by Sodium Toluenesulfonate for Highly Efficient Solar Cells. Issue 6 (6th April 2020) - Zhang, Mengmeng; Hu, Wanpei; Shang, Yanbo; Zhou, Weiran; Zhang, Wenfeng; Yang, Shangfeng
Abstract : Ionic defects at the surfaces of organolead halide perovskite films are detrimental to both the efficiency and stability of perovskite solar cells (PSCs). Herein, sodium p ‐toluenesulfonate (STS) is applied during the surface modification of perovskite layer for the first time, leading to the efficient surface passivation of the perovskite film and consequently significant enhancements in both efficiency and stability of mixed‐cation PSC devices. Upon incorporating STS atop the perovskite layer, the power conversion efficiency of the Cs0.05 MA0.12 FA0.83 PbI2.55 Br0.45 (abbreviated as CsMAFA) mesoporous‐structure mixed‐cation PSC devices improves from 18.70% to 20.05% with reduced hysteresis. The sulfonate (–SO3 − ) anion of STS coordinates with the Pb 2+ of CsMAFA perovskite, and the Na + cation of STS electrostatically interacts with the anions (I − /Br − ) of CsMAFA perovskite, resulting in the surface passivation of the CsMAFA perovskite film with reduced electron and hole trap state densities. In addition, STS modification induces an upshift of the valence band of perovskite, facilitating hole extraction from the perovskite layer to the hole transport layer with suppressed interfacial charge recombination. Moreover, such a trap state passivation of perovskite film leads to improvement of the ambient stability of PSC devices. Abstract : A nonhalogen organic salt sodium p ‐toluenesulfonate (STS) is applied during the surface modification of perovskite films for the first time, yielding an obvious enhancement of power conversion efficiency from 18.70% to 20.05% for perovskite solar cells, which originates from the surface passivation of the perovskite film with reduced trap state densities and suppressed interfacial charge recombination.